2010
DOI: 10.1007/s11095-010-0273-9
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystalization and Simultaneous Agglomeration Using Hot Melt Extrusion

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
124
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(128 citation statements)
references
References 34 publications
(33 reference statements)
2
124
0
Order By: Relevance
“…Enhancement in percent drug release could be due to better maintenance of micro-environmental pH, which results in higher solubility by inclusion of tartaric acid or formation of an in situ compound Xtartaric acid co-crystal solid dispersion. Similar results of dissolution enhancement due to formation of in situ co-crystals during hot melt extrusion of mixture of either API and coformer or API, coformer, and polymer carrier have been reported by other researchers (23,24). In the present study, however, much higher levels of impurities (∼10%) were observed for tartaric acid containing ternary ASD (formulation 5b), which could be related to degradation of tartaric acid as the tartaric acid degradation temperature of 175°C was close to the extrusion temperature of 165-170°C.…”
Section: Pvp Va64 Containing Amorphous Solid Dispersionssupporting
confidence: 89%
“…Enhancement in percent drug release could be due to better maintenance of micro-environmental pH, which results in higher solubility by inclusion of tartaric acid or formation of an in situ compound Xtartaric acid co-crystal solid dispersion. Similar results of dissolution enhancement due to formation of in situ co-crystals during hot melt extrusion of mixture of either API and coformer or API, coformer, and polymer carrier have been reported by other researchers (23,24). In the present study, however, much higher levels of impurities (∼10%) were observed for tartaric acid containing ternary ASD (formulation 5b), which could be related to degradation of tartaric acid as the tartaric acid degradation temperature of 175°C was close to the extrusion temperature of 165-170°C.…”
Section: Pvp Va64 Containing Amorphous Solid Dispersionssupporting
confidence: 89%
“…100) Several modified procedures, such as the addition of matrix polymers (e.g., polyvinyl caprolactam-polyvinyl acetate-polyethylene glycolgraft-copolymer), 101,102) have been reported. Applying process analytical technologies, such as Raman and near-IR spectroscopies, that enables in situ monitoring of product changes provides valuable information for controlling the mechanical manufacturing methods.…”
Section: Manufacturing Of Cocrystalsmentioning
confidence: 99%
“…These non-ionic interactions such as hydrogen bounds are very robust, so cocyrstal forms exhibit a high thermal stability and they are also very stable at high relative humidity, where salts are known to be unstable [11]. Although cocrystals can be formed by various methods such as solution crystallization [12,13], slurry conversions [14], ultrasonication [15,16] and melt processes [17,18], (wet or dry) grinding methods [19][20][21] are often preferred preparation methods based on their simplicity, eco-friendliness and high productivity [22]. Since wet-milling (i.e.…”
Section: Introductionmentioning
confidence: 99%